"Indirect Modification" of Glassy Carbon with Gold Nanoparticles Using Nonconducting Support Materials. Issue 4 (27th February 2013) - Nakashima, Daisuke; Marken, Frank; Oyama, Munetaka
Abstract Electrochemical measurements using nonconducting support materials, such as paper and cotton gauze, for modifying glassy carbon (GC) with gold nanoparticles (AuNPs) are described. After a seed‐mediated growth modification of AuNPs on Kimwipes, a AuNP‐Kimwipes‐modified GC electrode that was fabricated by simply fixing a piece of AuNP‐modified Kimwipes on a GC electrode surface showed almost reversible cyclic voltammetric responses for the oxidation of Fe(CN)64− in 0.1 M phosphate buffer solution (pH 7.0) even when the GC surface was not polished before fixing. The electrochemical impedance results also indicated the significant effect of the AuNP‐modified Kimwipes on reducing the charge transfer resistance. Similar effects were observed for AuNP‐modified cotton gauze, whose characteristics were the partial coverage of a GC surface, and, for the electrode in that a piece of untreated Kimwipes was bound between AuNP‐modified Kimwipes and a GC electrode surface. On the basis of such partial or remote effects of AuNPs together with other electrochemical results, plausible mechanisms to promote the electron transfer reaction of Fe(CN)64− by AuNPs are discussed. In addition, as a specific phenomenon in the present modified electrodes, the adsorption of Fe(CN)64− with the presence of AuNPs is described.